Safety and immunogenicity of a 15-valent pneumococcal conjugate vaccine in Japanese healthy infants: A Phase I study (V114-028) - Yasunori Ishihara; Haruo Kuroki; Hidenobu Hidaka; Kazuyuki Iwai; Keiko Wan; Masayoshi Shirakawa; Miyuki Sawata (Taylor & Francis Group, 2023)
This Phase I study evaluated the safety, tolerability, and immunogenicity of V114, a 15-valent pneumococcal conjugate vaccine (PCV), via subcutaneous (SC) or intramuscular (IM) administration, in healthy Japanese infants 3 months of age. A total of 133 participants were randomized to receive four doses (3 + 1 regimen) of V114-SC (n = 44), V114-IM (n = 45), or 13-valent PCV (PCV13)-SC (n = 44) at 3, 4, 5, and 12-15 months of age. Diphtheria, tetanus, and pertussis-inactivated poliovirus (DTaP-IPV) vaccine was administered concomitantly at all vaccination visits. The primary objective was to assess the safety and tolerability of V114-SC and V114-IM. Secondary objectives were to assess the immunogenicity of PCV and DTaP-IPV at 1-month post-dose 3 (PD3). On days 1-14 following each vaccination, the proportions of participants with systemic adverse events (AEs) were comparable across interventions, whereas injection-site AEs were higher with V114-SC (100.0%) and PCV13-SC (100.0%) than with V114-IM (88.9%). Most AEs were mild or moderate in severity and no vaccine-related serious AEs or deaths were reported. Serotype-specific immunoglobulin G (IgG) response rates at 1-month PD3 were comparable across groups for most shared serotypes between V114 and PCV13. For additional V114 serotypes 22F and 33F, IgG response rates were higher with V114-SC and V114-IM than with PCV13-SC. DTaP-IPV antibody response rates at 1-month PD3 for V114-SC and V114-IM were comparable with PCV13-SC. Findings suggest that vaccination with V114-SC or V114-IM in healthy Japanese infants is generally well tolerated and immunogenic.